The Recitation of Surah Al-Fath in the Ngeropok Tradition as a Living Qur’an Practice in Banten - Lathifa, Nadiyatul; Ghianovan, Jaka (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2024)
This study examines the communal recitation of Surah Al-Fath within the ngeropok tradition in Kepandean Kidul, Serang, as a form of Living Qur’an practice deeply rooted in the religious and cultural fabric of Banten’s Muslim community. Held during the Maulid al-Nabi celebration, the ngeropok ritual merges devotional worship with a symbolic tribute to the legacy of the Banten Sultanate. Adopting a qualitative case study approach, this research draws on participatory observation, in-depth interviews with religious figures and community members, and documentation of cultural artifacts. Thematic analysis, guided by the Miles and Huberman framework. Findings indicate that the recitation of Surah Al-Fath serves not only as a spiritual practice but also as a tafsīr praksis—a lived interpretation of the Qur’an that reinforces collective memory, social cohesion, and local Islamic identity. Despite adaptations in the digital era, such as evolving modes of communication and charitable giving, the tradition retains its core values of gratitude, unity, and spiritual reverence. This study underscores how local Islamic traditions like ngeropok embody dynamic expressions of sacred texts, continually reinterpreted in response to contemporary cultural and social contexts.